1000 artists' books : exploring the book as art - Salamony, Sandra; Peter & Donna Thomas (Firm) (Beverly, MA : Quarry Books, 2012)
Explores the book as an art form, including various aspects of hand-crafted books: covers, bindings, scrolls, folded and origami structures, books made from found objects, altered books, and book installations, as well as books created from a variety of printing processes.
Introduction --Codex books --Accordion and foldable books --Single-sheet books --Sculptural books --Image directory --Directory of artists --Acknowledgments --About the authors.
"Directory of artists": pages 313-319.